MicroRNA-150-3p enhances the antitumour effects of CGP57380 and is associated with a favourable prognosis in non-small cell lung cancer - Hongmei Zheng; Songqing Fan; Jiadi Luo; Qiuyuan Wen; Hongjing Zang (Scientific Reports)
Abstract MicroRNA (miRNA) dysregulation has been identified in several carcinomas, including non-small cell lung cancer (NSCLC), and is known to play a role in the development and progression of this disease. We initially conducted a miRNA microarray analysis, which revealed that the MNK inhibitor CGP57380 increased the expression of miR-150-3p. A similar analysis was performed using data from The Cancer Genome Atlas (TCGA). Cell proliferation, colony formation and migration assays were validated in A549 and H157 cells treated with miR-150-3p mimics. Quantitative polymerase chain reaction (qPCR) was then used to detect potential target genes. We observed significant downregulation of miR-150-3p in NSCLC samples compared with normal samples (P = 0.035). High miR-150-3p expression was associated with longer overall survival (P = 0.005), as determined via a tissue microarray (TMA). These results were validated in the TCGA and revealed that miR-150-3p was expressed at low levels in NSCLC tissues (P < 0.0001) and that patients with high miR-150-3p expression had a better prognosis (P = 0.042). Moreover, the combination of miR-150-3p and CGP57380 exerted a synergistic inhibitory effect on colony formation, growth, and migration and induced apoptosis in NSCLC cell lines. We investigated the potential targets of miR-150-3p and successfully validated six potential target genes through qPCR analysis. High miR-150-3p expression may enhance the response to immunotherapy, cisplatin and gemcitabine. In summary, this study underscores the promising therapeutic implications of combining miR-150-3p and CGP57380 for NSCLC treatment. Additionally, this study provides valuable insights into the molecular mechanisms underlying the effects of this treatment.